2021
DOI: 10.4102/sajce.v11i1.882
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of teacher training of reception teachers in implementing the pre-primary curriculum in Francistown, Botswana

Abstract: Background: Teachers emerge as main role players guiding the process of curriculum implementation across all levels of education. At early childhood development (ECD) level, curriculum implementation is unique, but emphasis on teacher training is essential as it influences teachers’ efficacy in promoting holistically developed children. Upon realising the significance of ECD, Botswana effected the Pre-primary Curriculum Framework (PCF) to guide teachers in teaching children.Aim: This article aims to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Hal tersebut disebabkan pelatihan berhubungan dengan kognitif, afektif, dan psikomotor guru, salah satunya konselor sekolah, sehingga perlu digalakkan. (Bawani & Mphahlele, 2021;Navarro-Montaño et al, 2021;Wegner, C., Wattenberg, L., Maar, A., & Gardow, D., 2017) menambahkan pelatihan penting bagi guru dan perlu digalakkan untuk meningkatkan kemampuan dan menjadikan guru sebagai panutan dan melayani siswa. Artinya pelatihan yang diperoleh guru memberikan pengalaman yang dapat dibagikan ke siswa untuk kegiatan yang sama, yaitu penulisan karya ilmiah.…”
Section: Hasil Dan Pembahasanunclassified
“…Hal tersebut disebabkan pelatihan berhubungan dengan kognitif, afektif, dan psikomotor guru, salah satunya konselor sekolah, sehingga perlu digalakkan. (Bawani & Mphahlele, 2021;Navarro-Montaño et al, 2021;Wegner, C., Wattenberg, L., Maar, A., & Gardow, D., 2017) menambahkan pelatihan penting bagi guru dan perlu digalakkan untuk meningkatkan kemampuan dan menjadikan guru sebagai panutan dan melayani siswa. Artinya pelatihan yang diperoleh guru memberikan pengalaman yang dapat dibagikan ke siswa untuk kegiatan yang sama, yaitu penulisan karya ilmiah.…”
Section: Hasil Dan Pembahasanunclassified
“…Lack of training constrains teachers to develop knowledge, skills, and attitudes for effective implementation of structured play activities. Bawani et al (2021) underscore that training of pre-primary teachers has a great impact on the implementation of curriculum. Likewise, Mabagala and Shukia (2019) observed that failure of the school administrators to identify training needs and recommend teachers for further training makes these teachers remain with limited knowledge and hence their efficiency in implementing structured play activities remains stagnated.…”
Section: Training Of Pre-primary Teachersmentioning
confidence: 99%
“…In response to the preceding statement, teachers can be said to play an important role in facilitating learners by involving the selection, arrangement, and delivery of information in a suitable environment (instructional media, materials, and teaching methods), as well as the way students interact with that information in classroom teaching and learning activities (Azizah et al, 2021;Bawani & Mphahlele, 2021;Torro et al, 2021). As a result, it is critical to ensure that teachers are aware of their students and that they are expected to actively participate in the teaching and learning process through integrated language teaching and learning (Chen & Yuan, 2021).…”
Section: Introductionmentioning
confidence: 99%